A Conformable Ultrasound Patch for Cavitation-Enhanced Transdermal Cosmeceutical Delivery - Yu, Chia-Chen (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.